The Impact of Public Budgets on Overall Productivity Growth - Heinz Handler; Andreas Knabe; Bertrand Koebel; Margit Schratzenstaller; Sven Wehke (Austrian Institute of Economic Research (WIFO), 2005)
To fulfil their tasks, governments rely on public expenditures and taxes. Both influence the incentives and shape the decisions and actions of private economic agents. As governments resort to both instruments simultaneously, their combined theoretical impact on economic performance is a priori indeterminate. Clarification can only come from empirical evaluations. This paper reviews the recent literature trying to quantify the impact of fiscal policies on productivity and growth. Unfortunately, this survey shows that the empirical literature too is inconclusive: although the growth and composition of public expenditures and taxes as well as the fiscal stance seem to have some effect in the short run, their long-run implications cannot easily be quantified because of, e.g., reverse causation and crowding-out effects. The empirical evidence on the growth effects of government size points at a non-linear relationship: For small governments additional public expenditures seem to have a positive impact on growth, while for large governments further additions tend to be growth-retarding. It is an open question, however, where the optimum is located.
Keywords: 330; Finanzpolitik; Produktivität; Wirtschaftswachstum; Öffentliche Ausgaben; Öffentlicher Haushalt; Steuer